Effect of different planes of nutrition and mineral supplementation on growth,nutrients utilization and semen quality of Frieswal bull calves - GIRDHAR, NARESH; MISHRA, A S; KUMAR, MAHESH; PRASAD, R (The Indian Journal of Animal Sciences, 2011)
Growing Frieswal bull calves (18) of approximately similar age and body weight (180 kg) were divided into 3 groups of 6 animals each. Animals of G 1 were fed as per Military farm feeding scale. Animals of G 2 were fed as per NRC (1989) whereas animals of G 3 were fed on 20% higher energy than NRC standard. Each group was further divided into 2 sub-groups A, B, thus making total of 6 sub groups i.e. G1A, G1B, G2A, G2B, G3A, and G3B. In subgroup A (Min 1), mineral supplementation was 2% of the concentrate mixture and in sub-group B (Min 2), the mineral supplementation was 3% of concentrate mixture. The feeding of roughage, green fodder and concentrate mixtures was done as per the requirement of animals with regular (fortnightly) recording of body weights. After a feeding period of 9 months, a digestibility trial of 7 days duration was conducted. The body weight of bull calves at the beginning of experiment was 183.0, 186.0, and 181.0 kg and increased to 458.0, 489.0 and 553.0 kg at the end of experiment (480 days) with average daily gain (ADG) of 574, 632 and 752 g in G 1, 2 and 3, respectively. It was significantly higher in the animals of G 3 as compared to G 1 and G 2, however within the groups there was not any significant difference. Dry matter intake (DMI) per 100 kg body weight was 2.46, 2.27 and 2.26 kg in the respective groups. Digestibility of nutrients for crude protein (CP), neutral detergent fibre (NDF), acid detergent fibre (ADF) and gross energy (GE) were apparently uniform in G 1 and 2 but were higher in G 3, however, DM and OM digestibility was significantly higher in the animals of G 3 as compared to G 1. DMI/100 kg BW and DEI (Mcal/d) was significantly higher in G3B than G3A. Similarily digestibility of DM, OM and CP was significantly higher in G1B than G1A. Effect on various semen quality parameters of bulls under trial indicated that mineral addition at 3% of concentrate mixture had positive effect on sperm percent motility, which was higher in Min 2 (43.04%) compared to Min I group (35.72%).